2010
DOI: 10.1371/journal.pone.0014003
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Are Required for Maintenance and Differentiation of Primary Lung Fibroblasts in Idiopathic Pulmonary Fibrosis

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is a progressive and fatal illness whose pathogenesis remains poorly understood. Recent evidence suggests oxidative stress as a key player in the establishment/progression of lung fibrosis in animal models and possibly in human IPF. The aim of the present study was to characterize the cellular phenotype of fibroblasts derived from IPF patients and identify underlying molecular mechanisms.Methodology/Principal FindingsWe first analyzed the baseline differentiation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(92 citation statements)
references
References 42 publications
(46 reference statements)
6
85
0
1
Order By: Relevance
“…Moreover, both the intracellular GSH level and total antioxidant capacity were decreased after treatment with TGF-b, which suggests that TGF-b may disturb the redox balance of corneal fibroblasts and promote the shifting of the cells into a state of oxidative stress. The results are consistent with previous studies reporting that TGF-b increased ROS production in numerous types of nonphagocytic cells, including aortic smooth muscle cells; prostatic stromal cells; hepatic stellate cells; and cardiac, lung, and skin fibroblasts (Hecker et al, 2009;Bocchino et al, 2010;Bondi et al, 2010;Michaeloudes et al, 2011;Sampson et al, 2011;Baek et al, 2012). It has been shown that TGF-b increases the activity of NAD(P)H oxidase and the expression of Nox2 and Nox4, and that both of these two homologs of the Nox family are the ones that mainly mediate the TGFb-induced ROS accumulation (Hecker et al, 2009;Jiang et al, 2010;Crestani et al, 2011;Sampson et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, both the intracellular GSH level and total antioxidant capacity were decreased after treatment with TGF-b, which suggests that TGF-b may disturb the redox balance of corneal fibroblasts and promote the shifting of the cells into a state of oxidative stress. The results are consistent with previous studies reporting that TGF-b increased ROS production in numerous types of nonphagocytic cells, including aortic smooth muscle cells; prostatic stromal cells; hepatic stellate cells; and cardiac, lung, and skin fibroblasts (Hecker et al, 2009;Bocchino et al, 2010;Bondi et al, 2010;Michaeloudes et al, 2011;Sampson et al, 2011;Baek et al, 2012). It has been shown that TGF-b increases the activity of NAD(P)H oxidase and the expression of Nox2 and Nox4, and that both of these two homologs of the Nox family are the ones that mainly mediate the TGFb-induced ROS accumulation (Hecker et al, 2009;Jiang et al, 2010;Crestani et al, 2011;Sampson et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…TGF-b stimulates reactive oxygen species generation, which in turn mediates myofibroblast differentiation (Sharma et al, 2009;Bocchino et al, 2010). To examine whether the myofibroblast differentiation of corneal fibroblasts by TGF-b treatment was mediated through enhanced ROS generation and accumulation, the cells were exposed to the NADPH oxidase (Nox) inhibitor DPI, the antioxidant NAC, or the Nrf2-ARE signaling activator sulforaphane, before the addition of TGF-b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IPF fibroblasts are known to maintain a profibrotic phenotype in ex vivo culture (53), and express constitutively higher nuclear SMAD3 (54,55). There have been very few studies that have investigated the regulatory mechanisms of constitutively active IPF fibroblasts (53,(55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…These efforts have demonstrated, among a host of changes, that IPF fibroblasts are more contractile (6), express higher concentrations of a-smooth muscle actin (a-SMA) (7,8), Type I collagen (8)(9)(10), and tissue inhibitors of metalloproteinase (11) than do normal lung tissue-derived fibroblasts, and are characterized by pathologic integrin signaling (12) and an invasive phenotype (13). Relative to normal cells, IPF-derived fibroblasts have also been shown to express lower concentrations of cyclooxygenase-2 (COX-2), produce less of the antifibrotic lipid mediator prostaglandin E 2 (PGE 2 ) (14,15), and exhibit resistance to this antifibrotic lipid mediator applied exogenously (16).…”
mentioning
confidence: 99%